2012
DOI: 10.1021/ma301679k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phosphonated Polyphosphazenes via Two Synthetic Routes

Abstract: Reagents. Tetrahydrofuran and triethylamine (EMD) were dried using solvent purification columns, and the final water content was monitored by Karl Fisher titration. 26 Ethanol and acetonitrile (EMD) were distilled from sodium metal and stored over molecular sieves (4Å) before use. Dichloromethane (EMD), methanol (EMD), hexanes (EMD), ethyl acetate (EMD), alanine ethyl ester hydrochloride (Chem Impex), phenylalanine ethyl ester hydrochloride (Chem Impex), sodium (Sigma), tyramine (TCI), ditert butyl dicarbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…40,41 The synthetic exibility of this system has provided access to biocompatible and biodegradable polymers that show good osteocompatibility 42,43 both in vitro 44,45 and in vivo, [44][45][46] with little acute inammatory response 47 and mineral deposition. 27 More recently, a number of phosphonic acid containing polyphosphazenes have been synthesized and characterized 48 in order to generate bioactive polymers capable of inducing in situ hydroxyapatite mineralization. In this work, their ability to mineralize hydroxyapatite from a simulated body uid (SBF) solution was examined.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 The synthetic exibility of this system has provided access to biocompatible and biodegradable polymers that show good osteocompatibility 42,43 both in vitro 44,45 and in vivo, [44][45][46] with little acute inammatory response 47 and mineral deposition. 27 More recently, a number of phosphonic acid containing polyphosphazenes have been synthesized and characterized 48 in order to generate bioactive polymers capable of inducing in situ hydroxyapatite mineralization. In this work, their ability to mineralize hydroxyapatite from a simulated body uid (SBF) solution was examined.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphosphazenes are commonly synthesized via a two-step reaction process starting from the commercially available cyclic trimer hexachlorocyclotriphosphazene (HCCTP). The first step involves the synthesis of linear PDCP which can be achieved via the controlled thermal ring opening polymerization of cyclic trimer at 250°C under vacuum [4, 10, 15, 21, 32, 37, 39, 40, 42, 44, 49, 56, 58-60]. This reaction is usually carried out under vacuum in a sealed glass tube at high temperatures; typically 250 °C for several hours.…”
Section: Synthesis Of Polyphosphazene – Mechanisms Of Polymerizationmentioning
confidence: 99%
“…Additionally, the hydrolytic breakdown is further facilitated by the hydrolytically labile nature of the PN bond linking the side group to the polymer backbone, which has been shown to be hydrolytically unstable even in the absence of acidic side groups . These hydrolysis rates are also significantly higher than those measured for the previously published phosphonic acid system, and can be explained by the significantly higher loading of acidic side groups in these polymers.…”
Section: Resultsmentioning
confidence: 81%
“…Previous work has shown that polyphosphazenes with biologically compatible side groups are biocompatible, have highly tunable rates of hydrolytic breakdown and are capable of producing a minimal inflammatory response when implanted in vivo . More recently, we have investigated polyphosphazenes containing phosphonic acid functionalized side groups, in an attempt to generate materials capable of nucleating the growth of hydroxyapatite during exposure to SBF . Although these materials were shown to have hydroxyapatite deposits on their surface, the coatings were sparse, with very little HAp deposited during the 4 week trial.…”
Section: Introductionmentioning
confidence: 99%